Answer:
The recursive formula is given below as
![\begin{gathered} a_1=7 \\ a_n=-3+a_((n-1)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pjnb48fnlqosk7ytnrvorv9834p5438xxn.png)
Step 1:
To figure out the value of the forurth term, we will substitute the value of
![n=4](https://img.qammunity.org/2023/formulas/mathematics/high-school/8kdg5auj18v9mli51cp6fk817r2dz5zyx9.png)
By substituting the n=4, we will have
![\begin{gathered} a_(n)=-3+a_((n-1)) \\ a_4=-3+a_((4-1)) \\ a_4=-3+a_3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/f7pudp9igrzjvmlu0ma2smd92vlht7pmgc.png)
Step 2:
Calculate the second term and the third term
![\begin{gathered} a_(n)=-3+a_((n-1)) \\ a_2=-3+a_((2-1)) \\ a_2=-3+a_1 \\ a_2=-3+7 \\ a_2=4 \\ \\ a_(n)=-3+a_((n-1)) \\ a_3=-3+a_((3-1)) \\ a_3=-3+a_2 \\ a_3=-3+4 \\ a_3=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uu2ispij6w6ui1kd4rlffhuct08xxm0f2h.png)
Step 3:
Substitute the value of the third term in the equation below
![\begin{gathered} a_(4)=-3+a_(3) \\ a_4=-3+1 \\ a_4=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1osg05h4t35ojttb7whjdqj8s1chygip0s.png)
Hence,
The final answer is
![\Rightarrow-2](https://img.qammunity.org/2023/formulas/mathematics/college/zwe4j8wqkxoskl60fgc4uz403vvloxh72b.png)
OPTION C is the right answer